Immunochemical biosensor for single virus particle detection based on molecular crowding polyelectrolyte system. Issue 24 (18th March 2022) - Baldina, Anna A.; Nikolaev, Konstantin G.; Ivanov, Artemii S.; Nikitina, Anna A.; Rubtsova, Maya Yu.; Vorovitch, Mikhail F.; Ishmukhametov, Aydar A.; Egorov, Alex M.; Skorb, Ekaterina V.
Abstract: To improve the effectiveness of the viral infection diagnostic, we offer a new approach of immunochemical biosensors to determine single viral particles by specific antibodies. The antibodies are immobilized on the electrodes in a three‐dimensional polymer matrix with several layers of polyelectrolytes on the screen‐printed carbon electrode. Non‐covalent immobilization of antibodies in successive layers of positively charged polyethyleneimine (PEI) and negatively charged polystyrene sulfonate (PSS) achieves the effect of macromolecular crowding. Such an immobilization approach promotes the preservation of the optimal conformation and antibody active center mobility for interaction with large virion particles. We established an electrochemical biosensor for tick‐borne encephalitis virus (TBEV) detection to demonstrate the method's applicability. Under the optimized architecture of the 3D‐matrix, including a combination of two layers of a positively charged PEI with antibodies and the last layer of a negatively charged PSS, the assay is characterized by an extremely low limit of detection (LOD). This LOD could be as few as five viral particles in a sample volume of 5 μl, which is two orders of magnitude lower than conventional ELISA with the same reagents. The advantage of the biosensor is also a wide linear range of detection from 10 3 to 10 9 viral particles/ml. The proposed principle for determining virion particles is well suited to novel express diagnostics and Point‐of‐Care viral infections detection. Abstract : The interaction of biomacromolecules in the medium of polyelectrolyte complexes makes it possible to preserve selective binding. The kinetics of the reaction in such a crowded medium, in the case of macromolecules, is comparable and exceeds the reactivity in solution.